2013
DOI: 10.5740/jaoacint.12-386
|View full text |Cite
|
Sign up to set email alerts
|

Modification of AOAC Official MethodSM 998.12 to Add Filtration and/or Centrifugation: Interlaboratory Comparison Exercise

Abstract: An international ring test was undertaken in 2012 among 10 international honey testing laboratories to examine the effects of filtration and/or centrifugation addition to AOAC 998.12 method (C4 sugar detection in honey). During protein extraction, when using the repetitive washing method, any insoluble material (i.e., pollen, dust) is coextracted along with protein which may result in contamination of the protein isotope value and result in a false-positive test. A modification step involving filtration and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 4 publications
(3 reference statements)
1
12
0
Order By: Relevance
“…To date, the factors underpinning this phenomenon are largely unexplained; however, work done by Rogers et al . (, , 2014a,b) has clearly shown that in many cases the current official methods (AOAC, ) are not sufficiently sensitive for C 4 level detection in some honeys and have called for a revision to the accepted protocols.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the factors underpinning this phenomenon are largely unexplained; however, work done by Rogers et al . (, , 2014a,b) has clearly shown that in many cases the current official methods (AOAC, ) are not sufficiently sensitive for C 4 level detection in some honeys and have called for a revision to the accepted protocols.…”
Section: Discussionmentioning
confidence: 99%
“…These non‐protein components may have isotope values which are considerably different from those of the pure protein, and can shift isotopic signatures away from true protein values (Rogers et al . , ). Briefly, 4 ml of distilled H 2 O was added to 10–12 g honey.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In doping control, it is used to confirm the endogenous steroid abuse by distinguishing the differences in the carbon isotope ratios of 13 C/ 12 C (or expressed as the carbon isotopic composition, δ 13 C) between the chemically synthesized and endogenously produced steroid hormones . Another important application of IRMS is the identification of food authenticity . Elemental analyzer coupled with IRMS was used to determine the presence of C4 (corn syrup or cane sugars) in honey by comparing the carbon isotopic value of whole honey with its internal protein .…”
Section: Introductionmentioning
confidence: 99%
“…Another important application of IRMS is the identification of food authenticity . Elemental analyzer coupled with IRMS was used to determine the presence of C4 (corn syrup or cane sugars) in honey by comparing the carbon isotopic value of whole honey with its internal protein . Furthermore, IRMS has been used for the discrimination of wild and farmed animal products.…”
Section: Introductionmentioning
confidence: 99%